(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Smith was born in Dublin on 3 June 1848 which was then part of the United Kingdom of Great Britain and Ireland. Smith wrote books on various rulers such as the Buddhist emperor, Ashoka and the Mughal emperor, Akbar, and a history of fine arts in India andCeylon. He also published two comprehensive volumes on Indian history, The Early History of India and The Oxford History of India. This paper analyzes about social aspects of ancient India in the views of V.S. smith